Shared Environment and Genetics Shape the Gut Microbiome after Infant Adoption - Hannah F. Tavalire (American Society for Microbiology, 2021)
Our results demonstrate that the early life home environment can significantly alter the gut microbiome in childhood, potentially altering health outcomes or risk for adverse health outcomes. A better understanding of the drivers of gut microbiome variation during childhood could lead to more effective intervention strategies for overall health starting in early life.